2005
DOI: 10.1038/sj.bjp.0706186
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide is a mediator of carrageenan‐induced hindpaw oedema in the rat

Abstract: Hydrogen sulphide (H 2 S) is a naturally occurring gas, with potent vasodilator activity. In this report, we identify a role for H 2 S in carrageenan-induced hindpaw oedema in the rat. Intraplantar injection of carrageenan (150 ml, 2% (w v À1 )) resulted in an increase in hindpaw H 2 S synthesising enzyme activity and increased myeloperoxidase (MPO) activity. Pretreatment (i.p. 60 min before carrageenan) with DL-propargylglycine (PAG, 25-75 mg kg À1 ), an inhibitor of the H 2 S synthesising enzyme cystathionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
104
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 19 publications
7
104
0
1
Order By: Relevance
“…This is a well-established model of joint inflammation. Intraplantar injection of carrageenan in the rat hindpaw resulted in an increase in the H 2 S synthesizing enzyme activity whilst pre-treatment with the CSE-inhibitor DL-propargylglycine (PAG) significantly reduced inflammation in a dosedependent manner in carrageenan-induced hindpaw edema (22).…”
Section: H 2 S As An Inflammatory Mediatormentioning
confidence: 99%
“…This is a well-established model of joint inflammation. Intraplantar injection of carrageenan in the rat hindpaw resulted in an increase in the H 2 S synthesizing enzyme activity whilst pre-treatment with the CSE-inhibitor DL-propargylglycine (PAG) significantly reduced inflammation in a dosedependent manner in carrageenan-induced hindpaw edema (22).…”
Section: H 2 S As An Inflammatory Mediatormentioning
confidence: 99%
“…A closer examination of the experimental protocol used in both studies suggests interlaboratory methodological differences could have accounted for these apparent contradictions. For example, Bhatia et al treated rats with 2% w/v solution of carrageenan for 3 h and added PAG intraplantar into one hindpaw 1 h before carrageenan treatment [40], whereas Zanardo et al performed time-course studies and used a 1.5% w/v solution, injecting BCA (or H 2 S donors) intraperitoneally 30 min prior to carrageenan treatment [41]. It is also possible that BCA and/or PAG exhibited effects independent of CSE inhibition, which modulated hindpaw fluid homeostasis (see later).…”
Section: H 2 S and Inflammatory Swelling (Edema)mentioning
confidence: 99%
“…Edema is commonly modeled in the laboratory through the use of carrageenan, a mucopolysaccharide extract of Chondrus crispus that induces an acute, defined and nonimmune inflammatory response [39]. Injection of carrageenan into the hindpaw of rats induced a significant increase in H 2 S synthesis and neutrophil infiltration, whereas pretreatment with PAG (a CSE inhibitor) resulted in dose-dependent inhibition of hindpaw edema and MPO activity [40]. In sharp contrast to this, a more recent study [41] showed the H 2 S 'donors' NaSH, sodium sulfide (Na 2 S) and Lawesson's reagent reduced leukocyte infiltration and adherence to the vascular endothelium via glibenclamide-inhibitable K ATP channels, and the CSE inhibitor BCA promoted leukocyte infiltration.…”
Section: H 2 S and Inflammatory Swelling (Edema)mentioning
confidence: 99%
“…3), metabolic hibernation (4,5), protection from ischemia/reperfusion injury (6 -10), oxygen sensing (11), vasodilatation (12,13), and promotion of angiogenesis (14). In common with nitric oxide, H 2 S is also implicated as both a pro- (15)(16)(17)(18) and antiinflammatory (18 -21) molecule in innate immune cells. Although the role of H 2 S signaling has been characterized in many other tissues and systems, it is unclear what role it plays in the regulation of the adaptive immune system.…”
mentioning
confidence: 99%